The AHA's 2020 Impact Goals: Moving toward Cardiovascular Health - Vinall, Phil (MD Conference Express, 2009)
In the late 1990s, the American Heart Association set a goal to reduce the rates of individual cardiovascular risk factors as well as death from CV causes by 25% by 2010. This article discusses the latest results on progress toward reaching those goals.